Effect of heat treatment on hardness and wear properties of an aluminum alloy of motorcycle piston - Mohd Fizam, Hj. Zainon
The present study was undertaken to investigate the effect of heat treatment on the microstructure, hardness and wear of aluminum alloys piston and with the aim to improve the mechanical properties by using heat treatment method. The material is from aluminum alloys piston; produced by one of Malaysian piston manufacturer and using on four-stroke of “National Motorcycle” engine. The as received piston contains alloying elements of Al, Si, Cu, Mg, Ni and Fe alloys with 8wt% Si. The solution treatment was performed at 500⁰C for 5 hours and then quenched in water at room temperature. Aging treatments were carried out at 130⁰C, 170⁰C and 210⁰C for 1 hour to 6 hours to observe the effect of aging condition on microstructure and mechanical properties. Microstructural analysis was carried out by using an optical microscope equipped with digital camera and a Scanning Electron Microscope (SEM). The hardness measurement was carried out by using a Vickers microhardness tester. A dry sliding wear test has been conducted by using pin on disk test. Volume loss, wear rate and wear coefficient were evaluated under un-lubricated conditions at loading conditions 10 N, sliding speeds 1.0 m/s, and sliding distances of 0.1, 0.25, 0.5, 1 and 2 km. The results showed, after full heat treatment the microstructure consists hard participates such as Al6Cu3Ni, β (Al5FeSi) and Mg2Si. The structure of Si particles form as acicular plate (rounded shape).Compare to as received, the results on microhardness after aging at 130⁰C show increases from 12.67% to 34%. While aging at 170⁰C shows increases from 28.06% to 46% and aging at 210⁰C shows increases from 25.29% to 44.36%. The result on wear test on the aged shows that was a reduction in wear rate 14.01% to 56.63% compared to that of as received. While, the wear coefficient of aging samples show lowest 3.09% to 42.15% from as received. The results showed that aging temperature of 170⁰C for 2 hr is the best condition the highest hardness and wear resistance of the aluminum alloys piston.